Evaluasi Ekonomi Penggunaan Antibiotika Profilaksis Cefotaxime dan Ceftriaxone pada Pasien Operasi Seksio Sesarea di Rumah Sakit X - Aisyah, Echa; Nadjib, Mardiati (Jurnal Ekonomi Kesehatan Indonesia, 2018)
A prophylactic antibiotic for patients with cesarean section surgery is highly recommended in the clinical guideline. The use of antibiotics is selected by using criteria safety and cost-effectiveness. This partial economic evaluation in the form of cost and outcome analysis was using alongside observational study method, prospective data were collected from April to May 2017 covering 60 patients with cesarean section surgery who received prophylaxis antibiotics, comparing cost-effectiveness between Cefotaxime and Ceftriaxone. The statistical test showed that there were no differences of characteristics in the 60 patients. The analysis based on the hospital perspective carried out in a public hospital in West Java. The Systematic Review showed that there was no difference in the efficacy of the drugs. This study confirmed that there was no difference in clinical outcome on surgical wound infections either in the patient who received Ceftriaxone prophylaxis or Cefotaxime. The greatest component of the cost was the operational cost (84.79%), followed by indirect cost (13.68%), investment cost (1.2%), and maintenance cost (0.32%). The analysis suggested the incremental cost was IDR342,535 in one episode of treatment. The hospital would save the cost of IDR317,529,945 a year by choosing Cefotaxime prophylactic antibiotics for patients with cesarean section surgery.